The importance of peak pricing in realizing system benefits from distributed storage. (October 2021) - Lavin, Luke; Apt, Jay
Abstract: A fundamental policy question for distributed energy resources (DER) is whether they create system benefits shared by all utility customers in addition to being profitable for the installing customer. This question has received considerable attention in "value of DER" and net metering reform proceedings for behind-the-meter solar photovoltaics in recent years. Commercial customer-sited lithium-ion batteries with a primary use case of demand charge management are forecast to greatly increase in the coming decade due to falling storage costs, making comparison of their customer and system benefits a timely topic in DER valuation. We conduct an overview of the system benefits of standalone commercial customer-sited storage on United States' electric tariffs and find system benefits will not be realized for many standalone commercial customer-sited storage installations in the absence of incentives for storage dispatch during the top 50–100 annual hours that drive grid infrastructure investment. Regulatory implementation of default peak pricing during a small subset of annual hours for customer-sited storage can realize additional system benefits and offer Pareto improvement. Additional transparency in regulatory estimates of these system benefits helps catalyze longer-term visions for increased competition at the retail level using DERs. Highlights: Commercial customer consumption peaks are not well-aligned with system peaks. Storage adoption optimized to minimize commercial bills is misaligned with system benefits. Critical peak pricing offers a Pareto improving solution for commercial customers with storage. Advanced rate design remains uncommon for U.S. commercial customers.